Pragmemes revisited. A theoretical framework - Capone, Alessandro; Graci, Roberto (Frontiers in Psychology, 2024)
In this paper, we take up an old issue that of pragmemes, broached by Mey and further explored by Capone. It is not easy to define pragmemes and distinguish them sufficiently from speech acts (units of language use broached by Austin and Searle) or from Wittgensteinian language games or from macro speech acts (see van Dijk on macrostructures) or from Goffman’s scripts. The best idea we could develop about pragmemes is that they instantiate the triple articulation of language, proposed by Jock Wong; being essentially composed of phonological-syntactic units, that have a certain content relative to a social situation and to a certain culture, pragmemes express a certain function (or illocutionary force), like, e.g., modifying society or some aspect of it. They are part of a chapter that can be called either “societal pragmatics” or “emancipatory pragmatics,” to use the words by Mey. In fact, knowledge of how language is used to diminish the rights of people and to propagate the “status quo” may be instrumental to give rights and power to ordinary human beings who are oppressed by political and economical structures.